A systematic approach for modeling and planning a sustainable electricity system in Colombia - Santiago Bernal-del Río; Nicolò Stevanato; Riccardo Mereu; Gilberto Osorio-Gómez (Energy Strategy Reviews)
One common method of defining and proposing energy transition dynamics involves using energy models to evaluate and establish action plans for the energy system. The precise characterization and definition of technical, economic and environmental specifications are crucial elements in obtaining reliable results from energy modeling. This article presents a comprehensive methodology for characterizing the energy system in Colombia, which enables the evaluation of various transition scenarios to decrease dependence on fossil fuels and reduce greenhouse gas emissions related to electricity generation. The primary contribution of this work is the development of a robust methodology that allows detailed characterization and flexible modeling of the energy system, providing a framework to generate different alternatives for the future of energy in Colombia, and serving as a valuable tool for other case studies. Collecting accurate demand and generation data, as well as constructing a transmission system model that accurately reflects the country’s electricity flow, are critical steps in the methodology. The proposed model was rigorously evaluated by exploring four different scenarios of system performance under varying conditions. Each scenario was assessed for different availability of water resources, replicating annual behaviors during ‘El Niño’ and ‘La Niña’ phenomena, and normal periods. The results confirm the feasibility of achieving a fully renewable electricity system in Colombia, demonstrating the country’s potential for significant decarbonization in its power sector. The clear increase in solar and wind energy usage, which accounts for up to 40% of total generation in the full renewable scenario, indicates that Colombia is capable of adopting clean and renewable technologies. This study highlights that with appropriate policies and investments, Colombia can transition to a sustainable and low-carbon energy future. The study applies an integrated technical, economic and environmental framework that evaluates four decarbonization pathways under three hydrological regimes, thereby capturing Colombia’s climate vulnerability and the cross-sector trade-offs often missed by single-discipline models.